Taxonomy of Central American water beetles in the genus Hydrochus Leach, 1817 (Coleoptera: Hydrochidae) - Perkins, Philip D. (Zootaxa, 2021)
The taxonomy of Central American water beetles in the genus Hydrochus Leach, 1817 is presented, including the Mexican fauna. The known fauna now consists of 26 species, nine of which are described as new species. The new species are diagnosed, and high-resolution images of the habitus and male genitalia of each species, and detailed descriptions of the male genitalia are given. Geographical distribution maps are given for all species. The following new species are described: H. aeruginosus n. sp. (Mexico), H. argutoides n. sp. (Costa Rica), H. biexcavatus n. sp. (Belize, Costa Rica, Honduras, Mexico, Nicaragua), H. laevigatus n. sp. (Mexico), H. lubricus n. sp. (Mexico), H. mesoamericanus n. sp. (Belize, Mexico), H. nayaritensis n. sp. (Mexico), H. panamensis n. sp. (Panama), and H. perpunctatus n. sp. (Mexico), Images of the habitus and male genitalia, and detailed descriptions of the male genitalia are also provided for the following previously described species: H. beeneni Makhan 1992, H. bernardi Makhan 1994, H. brianbrowni Makhan 2005, H. elineae Makhan 1994, H. foveatus Haldeman 1852, H. vagus LeConte 1852, H. vanvondeli Makhan 1994, and H. variolatus LeConte 1852. New locality data are provided for 17 species: H. beeneni Makhan 1992, H. bernardi Makhan 1994, H. brianbrowni Makhan 2005, H. debilis Sharp 1882, H. directus Perkins 2020, H. elineae Makhan 1994, H. foveatus Haldeman 1852, H. leei Perkins 2019, H. obscurus Sharp 1882, H. pertuberculatus Perkins 2020, H. piroei Makhan 1992, H. sagittarius Perkins 2019c, H. soekhnandanae Makhan 1992, H. steineri Perkins 2020, H. vagus LeConte 1852, H. vanvondeli Makhan 1994, and H. variolatus LeConte 1852. Lectotypes are designated for H. vagus LeConte 1852. H. otvosi Makhan 1993 is a new synonym of H. variolatus LeConte 1852.